Predictors of blood pressure levels, knowledge and practices of adult hypertensives attending a Secondary Health Care Centre in South-Western Nigeria - Azeez , Ismaheel Aderogba; Dairo, Magbagbeola David; Akinyemi, Joshua Odunayo; Idowu, Olufemi Philippe (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The prevalence of hypertension is increasing with accompanying poor control. The aim of this study was to assess the predictors of knowledge and practices of adult hypertensives. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was a prospective (before and after) study with health education as the intervention. A simple random sampling technique with computer-generated random numbers was used to recruit 386 patients. Data were analysed using SPSS version 23. Logistic regressions were used to determine the predictors of knowledge and practices. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Those who had tertiary education were about four times more likely to have good knowledge of hypertension than those who had secondary education (OR=0.256; 95% CI=0.106–0.617). The females were about 1.73 times more likely to have good practices of hypertension than males (OR=1.729; 95% CI=1.008–2.966). For every 1 unit increase in the body mass index, there was a statistically significant increase in diastolic blood pressure by about 0.22 units (95% CI=0.046–0.394, p=0.013). The health education had a positive impact on the blood pressure reduction. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The predictors of knowledge of hypertension, practices of hypertensives and diastolic blood pressure were level of education, sex, and body mass index respectively.